Development of SNP and microsatellite markers for goldsinny wrasse (Ctenolabrus rupestris) from ddRAD sequencing data - Jansson, Eva; Taggart, John; Wehner, Stefanie; Dahle, Geir; Quintela, Maria; Mortensen, Stein; Kvamme, Bjorn Olav; Glover, Kevin A (Conservation Genetics Resources, 2016)
Wrasse (Labridae) species have been used as parasite cleaners in Atlantic salmon farming since the 1980s. However, their use has recently escalated, with millions now being introduced into salmon cages each year. Most fish are of wild origin, their exploitation potentially impacting native populations. Genetic information is urgently required to inform management decisions. We identified 174 microsatellite and 149 SNP markers from ddRAD sequence data. From these, 17 and 48 microsatellite and SNP markers, respectively, were validated by genotyping 150 goldsinny wrasse collected from five locations along the Norwegian and Swedish coasts. Two to 30 alleles were identified at the microsatellite loci, while gene diversity (He) ranged 0.101–0.907. All SNP loci were biallelic, with averagedHeper locus ranging between 0.063 and 0.495.